Boundary layer analysis in nanofluid flow past a permeable moving wedge in presence of magnetic field by using falkner - skan model - Ali, Mohammad; Alim, Abdul MD (Zielona Góra: Uniwersytet Zielonogórski)
In the present work, the effect of various dimensionless parameters on the momentum, thermal and concentration boundary layer are analyzed. In this respect we have considered the MHD boundary layer flow of heat and transfer over a porous wedge surface in a nanofluid. The governing partial differential equations are converted into ordinary differential equations by using the similarity transformation. These ordinary differential equations are numerically solved using fourth order Runge?Kutta method along with shooting technique. The present results have been shown in a graphical and also in tabular form.
Keywords: MHD; nanofluid; wedge flow; porosity; convection